Coexistence of Primary Hyperaldosteronism and Graves’ Disease, a Rare Combination of Endocrine Disorders: Is It beyond a Coincidence—A Case Report and Review of the Literature - S. S. C. Gunatilake; U. Bulugahapitiya (Case Reports in Endocrinology, 2017)
Background. Primary hyperaldosteronism is a known cause for secondary hypertension. In addition to its effect on blood pressure, aldosterone exhibits proinflammatory actions and plays a role in immunomodulation/development of autoimmunity. Recent researches also suggest significant thyroid dysfunction among patients with hyperaldosteronism, but exact causal relationship is not established. Autoimmune hyperthyroidism (Graves’ disease) and primary hyperaldosteronism rarely coexist but underlying mechanisms associating the two are still unclear. Case Presentation. A 32-year-old Sri Lankan female was evaluated for new onset hypertension in association with hypokalemia. She also had features of hyperthyroidism together with high TSH receptor antibodies suggestive of Graves’ disease. On evaluation of persistent hypokalemia and hypertension, primary hyperaldosteronism due to right-sided adrenal adenoma was diagnosed. She was rendered euthyroid with antithyroid drugs followed by right-sided adrenalectomy. Antithyroid drugs were continued up to 12 months, after which the patient entered remission of Graves’ disease. Conclusion. Autoimmune hyperthyroidism and primary hyperaldosteronism rarely coexist and this case report adds to the limited number of cases documented in the literature. Underlying mechanism associating the two is still unclear but possibilities of autoimmune mechanisms and autoantibodies warrant further evaluation and research.